PERBANDINGAN HASIL BELAJAR MAHASISWA MENGGUNAKAN STRATEGI PQ4R DENGAN STRATEGI REHEARSAL ELABORASI DI STKIP TAPANULI SELATAN - Nasution, Nurhidayah Fithriyah (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
This research was aimed to know which one learning strategy was better between Preview, Question, Read, Reflect, Recite, Review (PQ4R) strategy andÂ Elaboration Rehearsal strategy in STKIP Tapanuli Selatan. The research sample was all students in semester V. The research method was quasi-experimental. The research result showed that studentâs learning outcomes who taught by using PQ4R strategy obtained the average value ( ) was 7,6 where deviation standard was 2,04 while students who taught by using Elaboration rehearsal strategy obtained the average value ( ) was 8,5 where deviation standard was 1,1. Based on the hypothesis testing obtained that Â tcount = 2,5 > dari ttable = 1,99 thus the Ha was accepted and Ho was rejected. Therefore can be concluded that studentâs learning outcomes who taught by using PQ4R strategy was better than studentâs who taught by using Elaboration Rehearsal strategy in STKIP Tapanuli Selatan.Â Key Words: PQ4R Startegy, Elaboration Rehearsal Strategy, Learning Outcomes.